Perancangan Intelligent Tutoring System Sebagai Upaya Inovatif Pada Pembelajaran Pemrograman Terstruktur - Khairunnisa Khairunnisa; Rismayanti Rismayanti (Query: Journal of Information Systems, 2020)
The development of computers and information technology helps develop and provide solutions to problems in other fields, one of which is in the field of education. What must be considered in education is the learning method. Every student has different abilities in understanding the material, one of them is Structured Programming Material. This subject is one of the basic materials that must be understood by students of Engineering and Computers. Seeing the limited meeting some students felt that they did not understand the material. Therefore, learning is needed that is able to help independent learning effectively. The development of science and technology is one of the computer media used in learning today. Intelligent Tutoring System (ITS)  is an interactive application program that implements artificial intelligence methods that can be used as information media and as evaluation media in the learning process. Furthermore, ITS can be used as a tool in independent learning for students. Then the purpose of this study is as a learning solution for students who cannot understand the Structured Programming program.Keywords: Learning, ITS, Structured Programming